2020
DOI: 10.36740/wlek202005120
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Cirrhosis: Liver Morphology and Function

Abstract: The aim was to establish the morphofunctional changes of liver in the experimental cirrhosis. Materials and methods: The research was conducted on 24 white male Wistar rats. Experimental cirrhosis of the liver was simulated by oral administration of CCl4 2 g/kg 2 times weekly for three months. From the selected fragments of the liver, histological specimens were done according to the conventional method and examined by light microscopy. The activity of the enzymes of cytolysis and cholestasis (ALT, AST, alkali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
1
3
0
2
Order By: Relevance
“…The present data revealed that the exposure to TAA increased serum ALT, AST, ALP and TB levels. Liver AST, ALT, ALP and TB are frequently used as biomarkers of liver injury and diseases ( Bozdağ and Eraslan, 2020 , Datsko et al, 2020 , Koyuncuoğlu et al, 2020 , Li et al, 2020 , Sun et al, 2021 ). Additionally, previous experimental studies showed that these parameters were significantly increased in animals exposed to TAA ( El-Baz et al, 2019 , Dwivedi et al, 2020 , Gowifel et al, 2020 , Bogahawaththa et al, 2021 , El-Gendy et al, 2021 , Younis et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The present data revealed that the exposure to TAA increased serum ALT, AST, ALP and TB levels. Liver AST, ALT, ALP and TB are frequently used as biomarkers of liver injury and diseases ( Bozdağ and Eraslan, 2020 , Datsko et al, 2020 , Koyuncuoğlu et al, 2020 , Li et al, 2020 , Sun et al, 2021 ). Additionally, previous experimental studies showed that these parameters were significantly increased in animals exposed to TAA ( El-Baz et al, 2019 , Dwivedi et al, 2020 , Gowifel et al, 2020 , Bogahawaththa et al, 2021 , El-Gendy et al, 2021 , Younis et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Different multi-center, double-blind, placebo-controlled trials, showed that the oral SAM treatment (800-1600 mg/day) induced a significant decrease of the clinical biochemical indices of cholestasis and an improvement of symptoms of fatigue and pruritus [152][153][154][155]. In another study, a systematic review and meta-analysis of randomized controlled trials (RCTs) evaluated the effect and safety of ursodeoxycholic acid (UDCA), SAM and UDCA-SAM combination therapies for intrahepatic cholestasis of pregnancy (ICP).…”
Section: Sam and Intra-hepatic Cholestasismentioning
confidence: 99%
“…At present the mechanisms determining the response to the treatment with Pegylated IFNα/Ribavirin are not completely known. A possible mechanism could be the HCV-induced viral interference with IFNα and JAK-STAT signaling, determined by the hypomethylation of STAT1 that facilitates the contact of STAT1 with its inhibitor PIAS1 (protein inhibitor of activated STAT1) [153]. In addition, two SNPs near the gene IL28B on chromosome 19 were found to be strongly associated with non-viral response [154,155].…”
Section: Sam and Viral Hepatitismentioning
confidence: 99%
“…24. № 1 статності [4], пов'язаний із підвищенням активності синтази оксиду азоту (NOS) з подальшим посиленням мікроперфузії печінки [5]. Однак залежний від оксиду азоту (NO) механізм дії LOLA при гострому токсичному ураженні печінки недостатньо вивчено.…”
unclassified